Integrated Support System For Tricycle Franchising - Charmie S. Calvo (International Journal of Advanced Science and Technology, 2020)
In the Ambisyon 2040, one of the foundations of sustainable development is ICT. The strategies are to expand the deployment of ICT infrastructure and address the gaps in digital connectivity. Therefore, government institutions must also integrate an e-system such as Mobile Application for Public Utility Vehicle particularly for the tricycles in Tuguegarao City to introduce ICT within the Franchising Municipal Office in monitoring the PUV-tricycles and to keep the passengers secured.            The Integrated Support System for Tricycle Franchising was developed to identify the problems and issues encountered by the franchising office, franchise owners, tricycle drivers and passengers with respect to application, registration, renewal, change of ownership, change of unit process, securing franchise, monitoring of violations, preparation and generation of reports. And, the extent of compliance of the developed system to ISO 25010, in terms of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability.The descriptive-developmental research design was utilized. There were 68 respondents which composed of franchising head, staff, IT Experts, tricycle drivers, franchise owners and passengers. It made use of an interview guide for the franchising office and survey questionnaire for the testing of the Integrated Support System using ISO 25010 standards. Frequency counts, percentages and mean was utilized in the treatment of data.The developed Integrated Support System for Tricycle Franchising benefited the Franchising office, franchise owners, passengers and tricycle drivers.